The Integration of World Capital Markets - Goldstein, Morris (IMF Working Papers; Working Paper, 1993)
This paper discusses the extent to which national capital markets have become linked, and identifies several of the more important consequences of that increased degree of integration. Alternative approaches to the measurement of capital market integration are reviewed, including deviations from the law of one price, differences between actual and optimally diversified portfolios, correlations between domestic investment and domestic saving, and cross-country links in consumption behavior. Two recent episodes of large-scale international capital flows-namely, the turmoil in the European Monetary System in the fall of 1992, and the surge of capital inflows into Latin America during the last three years-are examined for insights into the workings of today's global capital market. Finally, the paper offers some concluding remarks on the future development of international capital markets, on exchange rate management, on alternative approaches to living with larger and more influential financial markets, and on the financing of investment in the formerly centrally planned economies.